Resistance prediction of GRP bedar in calm water using computational fluid dynamic approach / Muhammad Haikal Daniel Jamal - Jamal, Muhammad Haikal Daniel (2022)
The term bedar, (in Terengganu spelled “bedor”), is applied to a wide variety of boats of the east coast of Malaysia that carry one or two junk sails and lack the typical transom stern of the perahu pinas. These junks rigged boats are usually built in Terengganu area. This type of boat is said to be an original Malay boat especially in terms of its shape. The upper part of the bow and back is mounted a piece of board protruding forward and backward as if the snout of a duck usually longer than the back. Apart from the hood at the back, in the middle of the hull of this boat there is a building known as “Jerombong”. The space below it is space filling stuff. The boat measures ten meters to sixteen meters and is about a width three meters. The loading rate of goods is estimated at around 350 to 400 pickups. The boat is propelled using three sails. The speed of this boat when sailing between 6 to 7 knots per hour.